Monitoring the Patient’s Blood Pressure Based on the Internet of Things (Lot) - Kamoun Alwan, Saleh Jabbar; Shahwaz Fattah, Mustafa Khalil; Hammadi Idan, Musa Jasim (American Journal of Botany and Bioengineering, 2025)
The growing demand for accessible and efficient healthcare services has accelerated the development of smart technologies for remote patient monitoring. Traditional blood pressure monitoring methods are limited by their reliance on manual readings and in-clinic visits, presenting challenges in continuous patient care. This study addresses this gap by designing an Internet of Things (IoT)-based system for real-time blood pressure monitoring. The system integrates Arduino-compatible sensors, ESP32 microcontrollers, and MQTT protocol for data transmission, alongside a mobile application interface for user accessibility. Alerts are automatically sent via Gmail when abnormal readings are detected. By analyzing case scenarios—normal, hypertensive, and hypotensive conditions—the system demonstrated its reliability in tracking fluctuations and enhancing early intervention. The implication of this technology lies in its potential to reduce hospitalization rates, support chronic disease management, and empower patients through continuous, home-based monitoring solutions.